Fermentation Volume Studies for Red Wine Experimentation - Sparrow, A.M.; Smart, R.E. (South African Journal of Enology and Viticulture, 2016)
Experimental vinification is often used to evaluate changes in viticultural and oenological practices in research trials. Microvinification procedures are used to overcome constraints that make standardised comparisons in commercial wineries difficult. Prior to 2009, a dedicated micro-winery research facility in northern Tasmania used conventional 12 L volume ferments that provided sufficient wine for both sensory and chemical analysis. Since then, much smaller ferment volumes of 1.5 L and of 250 mL have been introduced, and these provide a sufficient sample size for the chemical analysis of phenolic components in the wine. This study reports a comparison of the phenolic attributes of Pinot Noir wines in a replicated trial using must weights of 0.2, 1.0 and 10 kg fermented in vessels of volume 250 mL, 1.5 L and 20 L respectively. Using the same parcel of fruit, a single larger ferment of 330 kg and a vessel volume of 780 L was conducted concurrently. At bottling, six weeks after the end of fermentation, there was no significant difference in the phenolic composition of the wine made from grape musts with a mass of 0.2, 1.0 or 10 kilograms in the replicated trial, and the results were consistent with those for the 330 kg ferment size. We therefore have confidence in using small micro-scale fermenters, which greatly enhance research capability.